HTLV-1-Associated Myelopathy/Tropical Spastic Paraparesis Overlapping Ossification of the Ligamentum Flavum - Gago, Guilherme; Giacomini, Luidia Varrone; Gibbon, Frederico de Lima; Neto, Euripedes Gomes de Carvalho; Kowacs, Fernando; Ferreira, Nelson Pires (Indian Journal of Neurosurgery, 2020)
HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is an important cause of nontraumatic and noncompressive chronic myelopathy which generally has no improvement regardless of treatment. On the other hand, ossification of the ligamentum flavum (OLF) is also a cause of myelopathy; however, it can improve in some cases when surgical treatment is well applied. In this case report, we presented a case of a patient with HAM/TSP overlapping OLF which showed some improvement with surgical treatment.
Keywords: chronic myelopathy; tropical spastic paraparesis; ossification of the ligamentum flavum